2020
DOI: 10.1371/journal.pone.0244307
|View full text |Cite
|
Sign up to set email alerts
|

Acadesine suppresses TNF-α induced complement component 3 (C3), in retinal pigment epithelial (RPE) cells

Abstract: Rationale Age-related macular degeneration (AMD) is the most prevalent form of irreversible blindness in the developed world. Aging, inflammation and complement dysregulation affecting the retinal pigment epithelium (RPE), are considered significant contributors in its pathogenesis and several evidences have linked tumor necrosis factor alpha (TNF-α) and complement component 3 (C3) with AMD. Acadesine, an analog of AMP and an AMP-activated protein kinase (AMPK) activator, has been shown to have cytoprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Aging, inflammation, and dysregulation of the complement system affect the retinal pigment epithelium, and evidence has been found to involve tumor necrosis factor alpha and complement component 3 (C3) as one of the key factors in the development of age-related macular degeneration [6]. The primary effects of TNF are related to the cytoplasmic domain TNF-R1, which sequentially recruits death domains in a number of key signaling proteins: primarily the death domain associated with the TNF-α receptor (tumor necrosis factor receptor type 1associated via death domain protein, TRADD); Fas associated death domain (FADD); a starter of caspase-8 apoptosis (also known as FADD-like ICE, Fas-associated death domain-like IL-1β-converting enzyme, or FLICE), causing degeneration of numerous proteins [14].…”
Section: Discussionmentioning
confidence: 99%
“…Aging, inflammation, and dysregulation of the complement system affect the retinal pigment epithelium, and evidence has been found to involve tumor necrosis factor alpha and complement component 3 (C3) as one of the key factors in the development of age-related macular degeneration [6]. The primary effects of TNF are related to the cytoplasmic domain TNF-R1, which sequentially recruits death domains in a number of key signaling proteins: primarily the death domain associated with the TNF-α receptor (tumor necrosis factor receptor type 1associated via death domain protein, TRADD); Fas associated death domain (FADD); a starter of caspase-8 apoptosis (also known as FADD-like ICE, Fas-associated death domain-like IL-1β-converting enzyme, or FLICE), causing degeneration of numerous proteins [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ab-mediated complement activation or HMGB1 can contribute to enhance IFNγ secretion ( 53 , 54 ), which in turn can enhance C1s secretion ( 55 , 56 ) or NLRP3 inflammasome signaling ( 53 ). TNFα, which is amplified by HMGB1 in response to LPS ( 57 ), may trigger C3 or C1s secretion ( 58 , 59 ). Of note, it was early shown that IFNγ and TNFα are both secreted by human T cells as a response to C1q-bearing immune complexes, but not by non-opsonized complexes ( 60 ).…”
Section: Molecular Bases On Complement and Hmgb1 Multiple Functions W...mentioning
confidence: 99%
“…Likewise, different upstream stimuli may lead to activation of different cellular death pathways 31,32,[85][86][87] . For example, when ROS are the predominant cell death stimulus, ferroptosis (iron-dependent death) is the predominant pathway [87][88][89][90][91][92] ; whereas when tumor necrosis factor alpha (TNF-alpha) or FASL are the predominant stimuli, apoptosis and/or RIPK-dependent necrosis are the predominant pathways 24,25,31,32,86,[93][94][95][96] . To make things more complex, infiltrating immune cells also contribute to neurodegeneration via the inflammasome and cross-talk with several other pathways 80,85,[97][98][99][100][101][102][103][104][105][106] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 31 , 32 , 85 , 86 , 87 For example, when ROS are the predominant cell death stimulus, ferroptosis (iron-dependent death) is the predominant pathway, 87 , 88 , 89 , 90 , 91 , 92 whereas when tumor necrosis factor alpha and FAS/FAS ligand are the predominant stimuli, apoptosis and receptor interacting protein kinase–dependent necrosis are the predominant pathways. 24 , 25 , 31 , 32 , 86 , 93 , 94 , 95 , 96 To make things more complex, infiltrating immune cells also contribute to neurodegeneration via the inflammasome and cross-talk with several other pathways. 80 , 85 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 On the basis of these findings, we speculate that successful future approaches must target multiple pathways; optimal neuroprotection may require inhibition of upstream and downstream targets simultaneously because cellular death activation is stimulus dependent.…”
Section: Our Perspectivementioning
confidence: 99%